Factors Associated With Hepatitis A Mortality During Person‐to‐Person Outbreaks: A Matched Case–Control Study—United States, 2016‐2019. Issue 1 (19th April 2021) - Hofmeister, Megan G.; Xing, Jian; Foster, Monique A.; Augustine, Ryan J.; Burkholder, Cole; Collins, Jim; McBee, Shannon; Thomasson, Erica D.; Thoroughman, Douglas; Weng, Mark K.; Spradling, Philip R.
Abstract : Background and Aims: During 2016‐2020, the United States experienced person‐to‐person hepatitis A outbreaks that are unprecedented in the vaccine era, during which case–fatality ratios reported by some jurisdictions exceeded those historically associated with hepatitis A. Approach and Results: To identify factors associated with hepatitis A–related mortality, we performed a matched case–control study (matched on age [±5 years] and county of residence in a 1:4 ratio) using data collected from health department and hospital medical records of outbreak‐associated patients in Kentucky, Michigan, and West Virginia. Controls were hepatitis A outbreak–associated patients who did not die. There were 110 cases (mean age 53.6 years) and 414 matched controls (mean age 51.9 years); most cases (68.2%) and controls (63.8%) were male. Significantly ( P < 0.05) higher odds of mortality were associated with preexisting nonviral liver disease (adjusted odds ratio [aOR], 5.2), history of hepatitis B (aOR, 2.4), diabetes (aOR, 2.2), and cardiovascular disease (aOR, 2.2), as well as initial Model for End‐Stage Liver Disease (MELD) score ≥ 30 (aOR, 10.0), aspartate aminotransferase (AST)/alanine aminotransferase (ALT) ratio > 2 (aOR, 10.3), and platelet count < 150, 000/μL (aOR, 3.7) among hepatitis A outbreak–associated patients in the independent multivariable conditional logistic regression analyses (each model adjusted for sex). Conclusions: Preexisting liver disease, diabetes, cardiovascular disease, and initial MELD score ≥ 30, AST/ALT ratio ≥ 1, and platelet count < 150, 000/μL among hepatitis A patients were independently associated with higher odds of mortality. Providers should be vigilant for such features and have a low threshold to escalate care and consider consultation for liver transplantation. Our findings support the recommendation of the Advisory Committee on Immunization Practices to vaccinate persons with chronic liver disease, though future recommendations to include adults with diabetes and cardiovascular disease should be considered.